Revista Comunicación - Comunicación colaboradores, Revista (Revista Comunicación, 2016)
Colaboradores del número 1-2016
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTg4NDUvcmMudjI1aTEuMzAxMA